Effectiveness of resilience-based interventions in schools for adolescents: a systematic review and meta-analysis - Llistosella, Maria; Goni-Fuste, Blanca; Martín-Delgado, Leandra; Miranda-Mendizabal, Andrea; Franch Martinez, Berta; Pérez-Ventana, Carmen; Castellvi, Pere (Frontiers in Psychology, 2023)
Resilience has been identified as a dynamic process that provides capabilities to face adversity. Considering the many protective factors involved in resilience and that the school is a key context to promote resilience, this review aimed to examine the effect of school-based interventions on resilience in adolescents. Methods A systematic literature review and meta-analysis were conducted in July 2021 on four databases. The risk of bias was assessed using the Cochrane risk of bias tool. Random-effects meta-analysis was used to obtain pooled estimates. Stratified analyses were done according to population type (general, at risk), intervention type, and follow-up assessments.Of the 1,667 articles obtained, 27 were included in the systematic review and 16 in the metaanalysis. The random effects indicated a significant increase in resilience after the intervention (SMD = 0.58, 95% CI [0.29-0.87]). Subgroup analysis showed effectiveness only in population at risk (SMD = 1.28, 95% CI [0.53-2.03]) and early adolescence (SMD = 1.28, 95% CI [0.42-2.14], PI [-7.44-10.33]). Multicomponent intervention (SMD = 1.45, 95% CI [0.11-2.80]) and Cognitive Behavioural Therapy (CBT) (SMD = 0.20, 95% CI [0.06-0.34]) demonstrated significant effectiveness. Significant results were observed only for 8-weeks follow-ups or less (SMD = 1.55, 95% CI [0.61-2.48]).These findings provide evidence that Multicomponent and CBT interventions increase resilience in early adolescents at risk only in the short term. Developing resilience interventions is useful in schools exposed to an unfavourable socio-economic context. Furthermore, longterm interventions should be redesigned to improve their effectiveness.